INNOVATIVE LEADERSHIP STRATEGIES FOR SCHOOL PRINCIPALS: BUILDING A HOLISTIC EDUCATIONAL ENVIRONMENT FOCUSED ON STUDENT ACHIEVEMENT IN THE ERA OF TECHNOLOGY AND GLOBALIZATION - Frederikus Fios; Marzuki; Ibadurrahman; Axelon Samuel Renyaan; Eliagus Telaumbanua (Adisam Publisher, 2024)
Educational leadership, mainly embodied by school principals, serves as the linchpin in shaping the trajectory of academic institutions. This abstract critically scrutinizes the multifaceted realm of innovative leadership strategies employed by school principals to forge a holistic educational environment centered on optimizing student achievement. A nuanced synthesis of critical findings unravels the intricacies of technological integration, global perspectives, and the establishment of a comprehensive educational milieu. The identified keywords— Innovative Leadership, School Principals, Holistic Education, Student Achievement, Technology, and Globalization—serve as beacons, encapsulating the core facets of this exploration. This study substantially contributes to the ongoing discourse on educational leadership by offering nuanced insights into effective strategies meticulously tailored for the contemporary era dominated by technology and globalization. As crucial change agents, principals are explored in their dynamic roles, navigating challenges and fostering environments conducive to meaningful student growth. The emphasis on technological integration reflects the pivotal role of visionary leaders in preparing students for the demands of the 21st century. Additionally, the global perspective highlights the importance of educators embracing diverse cultural perspectives, fostering international collaborations, and cultivating students' skills for an interconnected world. The study advances discussions on educational leadership by shedding light on practical applications, challenges, and future research directions, contributing valuable knowledge to the evolving landscape of educational practices,.